Zapomniana inwestycja . Niezrealizowana koncepcja budowy Wojewódzkiego Szpitala Specjalistycznego w Zielonej Górze - Skobelski, Robert (In Gremium. Studies in History, Culture and Politics, 2015)
Forgotten investment . Shelved project – construction of the Regional Specialist Hospital in Zielona Góra Development of the Regional Hospital in Zielona Góra in the seventies of the last century did not keep up with the increasing number of the town inhabitants. The facility suffered from the lack of premises the most important of which was the lack of specialist wards. Similar difficult conditions were characteristic for the majority of the other hospitals operating at the time in the Province. In view of the problem central authorities decided to construct a new specialist hospital in Zielona Góra. Unfortunately, the project was never implemented due to the escalating political and economic crisis at the turn of the seventies. The idea of building the hospital was approached again in the middle of the eighties. Several relevant designs for the construction were made then and the Social Committee for the Construction of the Regional Hospital was appointed to solicit the necessary funds. The works on the first facility of the future hospital started in 1988 – it was a housing facility for medical staff. Unfortunately, in the beginning of the nineties, in view of new economic conditions as a result of the economic and political restructuring, the project was finally abandoned, mainly because of financial reasons.